The Role of the Holy Spirit during Parousia in the Eschatology of Sergius Bulgakov - Maciej Raczyński-Rożek (Polonia Sacra)
In Parousia, Jesus Christ is undoubtedly the central figure. However, since Parousia is the revelation of the glory of the entire Trinity, it is worth asking about the role of the remaining Divine Persons in this event. In the article, the main focus will be on the role of the Holy Spirit and its interpretation in the eschatology of Sergius Bulgakov. According to the Russian theologian, Parousia is a revelation not only of Christ’s glory, but also of the hypostatic Glory of God, i.e. the Holy Spirit, and in this way it’s the final realization of Pentecost.